Repeated Exposure to D-Amphetamine Decreases Global Protein Synthesis and Regulates the Translation of a Subset of mRNAs in the Striatum - Biever, Anne; Boubaker-Vitre, Jihane; Cutando, Laura; Gracia-Rubio, Irene; Costa-Mattioli, Mauro; Puighermanal, Emma; Valjent, Emmanuel (Frontiers in Molecular Neuroscience, 2017)
Repeated psychostimulant exposure induces persistent gene expression modifications that contribute to enduring changes in striatal output neurons (SPNs). However, it remains unclear whether changes in the control of mRNA translation are required for the establishment of these durable modifications. Here we report that repeated exposure to d-amphetamine decreases global striatal mRNA translation. This effect is paralleled by an enhanced phosphorylation of the translation factors, eIF2α and eEF2, and by the concomitant increased translation of a subset of mRNAs, among which the mRNA encoding for the activity-regulated cytoskeleton-associated protein, also known as activity regulated gene 3.1 (Arc/Arg3.1). The enrichment of Arc/Arg3.1 mRNA in the polysomal fraction is accompanied by a robust increase of Arc/Arg3.1 protein levels within the striatum. Immunofluorescence analysis revealed that this increase occurred preferentially in D1R-expressing SPNs localized in striosome compartments. Our results suggest that the decreased global protein synthesis following repeated exposure to d-amphetamine favors the translation of a specific subset of mRNAs in the striatum.